Assessment of Specialists' Level of Adaptation to the Conditions of Society in Transformation - A E Nizamova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2012)
The author focuses her attention on the analysis of the general and the particular in the adaptation of specialists on the basis of the data collected in Russia by the NRI HSE in the course of monitoring the population's economic situation and health (RLMS-HSE), comprising a vast body of classified information on the changes in the conditions and quality of life of the Russian people.